2007
DOI: 10.1080/02652030600988020
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological detection of 10 quinolone antibiotic residues and its application to artificially contaminated poultry samples

Abstract: To assess if microbiological inhibition tests for detection of antibiotic residues are suitable for routine screening for quinolone residues, the limit of detection (LOD) of 10 different quinolones and fluoroquinolones was determined. Two media were tested, one at pH 6 and the other at pH 8, each seeded with one of the following test strains: Bacillus subtilis, Escherichia coli or Bacillus cereus. LODs of the 10 substances were highest on plates seeded with B. cereus, intended for selective detection of tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 9 publications
0
16
0
4
Order By: Relevance
“…The study has evaluated and compared the sensitivity of the method with a strain of E. coli to quinolones and differences in the sensitivity of the medium at pH 6 and 8. The plate with E. coli at pH 8 was more sensitive and detected 5 quinolones out of 8 at levels ≤ MRL in poultry meat (Okerman et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The study has evaluated and compared the sensitivity of the method with a strain of E. coli to quinolones and differences in the sensitivity of the medium at pH 6 and 8. The plate with E. coli at pH 8 was more sensitive and detected 5 quinolones out of 8 at levels ≤ MRL in poultry meat (Okerman et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For all these residues E. coli ATCC 128 appeared to be superiorly sensitive and this organism was recommended for supplementing the existing microbial screening tests. A third comparative study evaluated the susceptibility of the same organisms as in [39] for ten different quinolones [41]. Only difloxacin appeared to be detected more sensitively using B. subtilis as the test organism.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Differences between tissue matrices could explain this disagreement since antimicrobial residue concentration in matrices such as kidney was reported to be higher than concentration in muscle samples. Therefore some authors (Okerman et al 2007) have concluded that it should be advisable to use kidney rather than muscle samples as the test material for analysis of residues in animals. However, muscular antimicrobial concentration is more relevant for consumer safety than kidney levels.…”
Section: Quantification Of Antimicrobials In Incurred Tissue Samplesmentioning
confidence: 98%
“…The suitability of E. coli for screening of different quinolone residues was also determined using standard solutions in media with different pH values (Okerman et al 2007). The lowest limits of detection observed for enrofloxacin, ciprofloxacin, marbofloxacin, norfloxacin, sarafloxacin, danofloxacin, difloxacin and flumequine were 0.625, 1.25, 2.5, 5, 5, 1.25, 40 and 5 µg/kg, respectively.…”
Section: Quantification Of Antimicrobials In Incurred Tissue Samplesmentioning
confidence: 99%